2009
DOI: 10.1038/sj.bjc.6604839
|View full text |Cite
|
Sign up to set email alerts
|

A humanised anti-IGF-1R monoclonal antibody (AVE1642) enhances Bortezomib-induced apoptosis in myeloma cells lacking CD45

Abstract: The humanised form of an antagonistic anti-IGF-1R mAb (AVE1642) selectively inhibits the growth of CD45 neg myeloma cells. AVE1642 strongly increased bortezomib-induced apoptosis, correlated with an increase of Noxa expression. These results support the therapeutic use of anti-IGF-1R/bortezomib in CD45 neg Myeloma patients, particularly those with the most aggressive form, t(4,14).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…We have previously shown that AVE1642 was able to inhibit the proliferation of CD221 positive-CD45 negative, but not that of CD221 positive-CD45 positive human myeloma cell lines, and that the overexpression of CD221 in CD45-positive human myeloma cell lines was not sufficient to induce AVE1642 sensitivity. 4,8 On the contrary, extinction of CD45 by shRNA in CD45 positive human myeloma cell lines was able to induce AVE1642 sensitivity. In the present study, CD45 phenotype was evaluated in 23 out of 26 patients, and was negative in 16 cases (70%).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that AVE1642 was able to inhibit the proliferation of CD221 positive-CD45 negative, but not that of CD221 positive-CD45 positive human myeloma cell lines, and that the overexpression of CD221 in CD45-positive human myeloma cell lines was not sufficient to induce AVE1642 sensitivity. 4,8 On the contrary, extinction of CD45 by shRNA in CD45 positive human myeloma cell lines was able to induce AVE1642 sensitivity. In the present study, CD45 phenotype was evaluated in 23 out of 26 patients, and was negative in 16 cases (70%).…”
mentioning
confidence: 99%
“…AVE1642 has been able to delay growth and survival of some cancer cells in vitro, human tumor xenografts in nude mice, and to inhibit proliferation and survival of most MM cells (primary cells from patients or MM cell lines). 4 The present phase 1, multicenter, 2-part study, open-label, was to explore the dose to be selected for further development of AVE1642 (dose escalation design, part 1), to evaluate pharmacokinetics (clearance of the antibody) and pharmacodynamics (IGF-1 serum levels) of AVE1642 alone and in combination with bortezomib, and to assess the safety of the combination of AVE1642 (at the selected dose), with the recommended dose of bortezomib in patients with relapsed MM (Part 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AVE1642 inhibits growth and increases bortezomib-induced apoptosis of aggressive human myeloma cells in vitro [159]. Based on these results, a phase I clinical study of AVE1642 in combination with the proteasome inhibitor bortezomib was conducted in patients with relapsed multiple myeloma.…”
Section: Anti-insulin-like Growth Factor Receptor I (Anti-igf-ir)mentioning
confidence: 99%
“…60 The mechanism of synergy between AVE1642 and bortezomib may be related to synergistic upregulation of Noxa, which induces the release of the BH3-only activators that are responsible for Bax activation. 60 On the basis of these results and phase 1 data, which showed good tolerability of AVE1642 in advanced myeloma (except for grade 3 hyperglycemia in diabetic patients), 61 the combination of AVE1642 and bortezomib was tested in relapsed/refractory myeloma. Although this combination was well tolerated, response rate was low with at least PR in only 18% of patients.…”
Section: Il-6 and Il-6 Receptormentioning
confidence: 99%